2014
DOI: 10.1136/jclinpath-2014-202514
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of adrenocortical carcinoma reveals new routes to targeted therapies

Abstract: AimsAdrenocortical carcinoma (ACC) carries a poor prognosis and current systemic cytotoxic therapies result in only modest improvement in overall survival. In this retrospective study, we performed a comprehensive genomic profiling of 29 consecutive ACC samples to identify potential targets of therapy not currently searched for in routine clinical practice.MethodsDNA from 29 ACC was sequenced to high, uniform coverage (Illumina HiSeq) and analysed for genomic alterations (GAs).ResultsAt least one GA was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…In this report of a precision medicine approach for advanced ACCs, including NGS, IHC, and FISH, we sought to verify our results in the light of previously published precision medicine studies for ACC [11, 12]. We identified 4 samples with at least 1 mutation in our 50-gene panel.…”
Section: Discussionmentioning
confidence: 66%
“…In this report of a precision medicine approach for advanced ACCs, including NGS, IHC, and FISH, we sought to verify our results in the light of previously published precision medicine studies for ACC [11, 12]. We identified 4 samples with at least 1 mutation in our 50-gene panel.…”
Section: Discussionmentioning
confidence: 66%
“…Overall, 19/40 ACCs (47.5%) had at least one molecular abnormality (De Martino et al 2013). In a second study, Ross et al (2014) recently performed a comprehensive genomic profiling of 29 ACC samples and found at least one alteration (a mutation, amplification, deletion, or truncation) in 22 cases (76%). Genomic alterations in NF1 (14%), CDKN2A (14%), ATM (10%), CCND2 (7%), CDK4 (7%) and DNMT3A (7%) were considered as the most common and potentially clinically relevant at the same time (Ross et al 2014).…”
Section: Geneticsmentioning
confidence: 99%
“…In a second study, Ross et al (2014) recently performed a comprehensive genomic profiling of 29 ACC samples and found at least one alteration (a mutation, amplification, deletion, or truncation) in 22 cases (76%). Genomic alterations in NF1 (14%), CDKN2A (14%), ATM (10%), CCND2 (7%), CDK4 (7%) and DNMT3A (7%) were considered as the most common and potentially clinically relevant at the same time (Ross et al 2014). The third study showed, considering the different omics classifications, a strong correlation between clustering of patients with different prognosis based on transcriptome clusters, DNA methylation and miRNA expression .…”
Section: Geneticsmentioning
confidence: 99%
“…These studies converge on a reduced list of recurrent ACC drivers (Table 1). Two other studies used next generation sequencing to characterize the mutations in ACC, analyzing the genetic variation of a limited number of cancer-related genes, and restricting the analysis to the tumor DNA (35,36).…”
Section: The Mutation Landscape Of Acc: a Reduced Number Of Genes Witmentioning
confidence: 99%
“…Concerning methylation, the CIMP can be recapitulated by focal measurements of methylation, using methylation-specific multiplex ligation probe assay, a technique widely available in oncogenetic departments (59). Finally targeted sequencing of driver genes can be performed by next generation sequencing (35,36). In theory all these techniques are easily applicable.…”
Section: Genetic Counseling For the New Genetic Diseasesmentioning
confidence: 99%